2D Atomic Crystals: A Promising Solution for Next‐Generation Data Storage. (29th March 2019) - Hou, Xiang; Chen, Huawei; Zhang, Zhenhan; Wang, Shuiyuan; Zhou, Peng
Abstract: With the rapid development of the information age, more and more new technologies such as big data and cloud computing are beginning to emerge. As a result, the demand for high data‐storage density is becoming more and more urgent. In the past 10 years, data‐storage density has been greatly improved by reducing the size of memory cells. However, as semiconductor technology nodes have shrunk, a number of problems have appeared in metal–oxide–semiconductor field‐effect transistor (MOSFET)‐based memory cells, such as gate‐induced drain leakage, drain‐induced barrier lowering, and reliability issues. Fortunately, due to their atomic thickness, high mobility, and sustainable miniaturization properties, 2D atomic crystals (2D materials) are considered the most promising substitute for silicon to solve those issues. This review investigates the use of 2D materials in nonvolatile and volatile memories, including MOSFET‐based memory, magnetic random‐access memory, resistive random‐access memory, dynamic random‐access memory, semi‐floating‐gate memory, and other novel memories. Abstract : An overview of how 2D materials are applied in data storage is provided. Unique and beneficial properties (such as large on/off ratio, ultrathin bodies, and rich band structure) mean 2D material‐based memory devices exhibit desirable data storability. Considering that silicon‐based memory technology is approaching its physical limits, 2D materials might be a promising solution for next‐generation data storage.